Bias in administrative decision making: focusing on local government - Smit, Henrietta Augusta (Department of Private Law, 2021)
The Centre for Local Government Training, Western Cape, has been running a training/orientation programme for local government councillors since the beginning of 1996. ' As part of this programme, I have had the opportunity to conduct the training of a basic module on local government and administrative law for several transitional local councils. From the numerous questions asked in this regard, it soon became clear that many councillors were uncertain as to when they had to recuse themselves from council meetings on the grounds of bias, or a possibility of bias. Not surprisingly, as the test for bias in non-judicial administrative decision making is far from clear, even to lawyers, many councillors appeared to have difficulty in applying the test to their personal circumstances. It is hoped that this dissertation, in shortened and simplified form, can serve as a practical guide to councillors in this regard. After all, prevention is better than cure, and any unnecessary court proceedings that can be avoided, will be saving the ratepayers thousands of rands. At the outset, the rules of natural justice will be briefly discussed, as well as section 33 of the Constitution of the Republic of South Africa, no 108 of 1996. This will be followed by a detailed discussion of the rule against bias: including the test to be applied; the grounds for the appearance of disqualifying bias illustrated by a discussion of case law; the issue of departmental bias; the consequences of impermissible bias; and the doctrine of necessity. The focus will then move to local government, and the relevant legislation as expounded by the courts. Finally, the consequences of a biased decision in local government will be looked at, and the constitutionality of certain sections of the local government ordinances questioned.